The Effect of Work Life Balance on Millennial Generation Productivity in Makassar City - M. Hidayat; Aulia Aulia (Borong Newinera Publisher, 2023)
This study aims to determine the effect of Work Life Balance on the productivity of the millennial generation in Makassar City. This research is a descriptive study with a quantitative approach with data analysis techniques used simple linear regression and hypothesis test consist of t test and coefficient of determination. The results of the study show that Work Life Balance has a positive and significant influence on the productivity of the millennial generation in Makassar City. The concept of work life balance is expected to be applied in suppor productivity, especially in the millennial generation.